1989
DOI: 10.1093/oxfordjournals.aje.a115336
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Rota Virus Infection and Gastroenteritis in Prospectively Monitored Argentine Families With Young Children

Abstract: A prospective study was carried out in 49 families of newborns in Avellaneda District, Argentina, recruited when the mother was in the last trimester of pregnancy and followed until the newborn was aged two years, to study the epidemiology of rotavirus infection under natural conditions. Weekly surveillance of all family members for diarrhea and rotavirus-related diarrhea was carried out from May 1983 to July 1986. Serum samples were also collected every six months to study the incidence of rotavirus infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
10

Year Published

1991
1991
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 0 publications
0
30
0
10
Order By: Relevance
“…The overall incidence of diarrhoea in the total study population was 0-9 cases per person-year and the peak incidence of diarrhoea in children aged <2 years was 2-1 cases per person-year [13]. The incidence of EAV-associated diarrhoea in the overall population was 2-9 cases per 100 person-years.…”
Section: Independent Identification Of Ea Vmentioning
confidence: 82%
See 4 more Smart Citations
“…The overall incidence of diarrhoea in the total study population was 0-9 cases per person-year and the peak incidence of diarrhoea in children aged <2 years was 2-1 cases per person-year [13]. The incidence of EAV-associated diarrhoea in the overall population was 2-9 cases per 100 person-years.…”
Section: Independent Identification Of Ea Vmentioning
confidence: 82%
“…In the same population we have shown that 10-5 % of diarrhoea cases were associated with rotavirus in children <2 years old [13]. However in 85 % of the cases the aetiology remained unknown and probably enteric parasites and enteropathogenic bacteria have a relevant role.…”
Section: Independent Identification Of Ea Vmentioning
confidence: 84%
See 3 more Smart Citations